2021
DOI: 10.1029/2020jg005876
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Changes in the Flux of Atmospheric Nitrate From a Forest Canopy to the Surface Soil Based on Δ17O Values

Abstract: The vertical profiles of the proportion of atmospheric NO 3 − to total NO 3 − were different from those of atmospheric NO 3 − flux • The forest canopy retained a large portion of the deposited atmospheric NO 3 − • The retention rates of atmospheric NO 3 − were different among different canopy types Supporting Information:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 79 publications
(204 reference statements)
0
7
0
Order By: Relevance
“…Accordingly, it can be concluded that the replenishment of 𝐴𝐴 p-NO3 − and 𝐴𝐴 n-NO3 − was generally higher than the loss of 𝐴𝐴 b-NO − retention, which caused higher fluxes of 𝐴𝐴 t-NO3 − than 𝐴𝐴 b-NO3 − (Figure 3b). Lower 𝐴𝐴 Δ 17 Ot-NO 3 − than the corresponding 𝐴𝐴 17 Ob-NO 3 − (by −4.5 ± 6.5‰ for broadleaved forests and −2.7 ± 1.5‰ for coniferous forests; Figure 4) verified the microbial nitrification within canopies as a significant 𝐴𝐴 NO3 − utor to 𝐴𝐴 t-NO3 − (Guerrieri et al, 2015(Guerrieri et al, , 2020Inoue et al, 2021;Shi et al, 2014). This finding was supported by the generally lower 𝐴𝐴 𝐴𝐴 18 Ot-NO 3 − and 𝐴𝐴 𝐴𝐴 15 Nt-NO 3 − signatures relative to the corresponding 𝐴𝐴 𝐴𝐴 18 Ob-NO 3 − and 𝐴𝐴 𝐴𝐴 15 Nb-NO 3 − values, respectively (Figure 4).…”
Section: Higher 𝑨𝑨 No𝟑𝟑 − Deposition Fluxes In Throughfall Than In Bu...mentioning
confidence: 80%
See 4 more Smart Citations
“…Accordingly, it can be concluded that the replenishment of 𝐴𝐴 p-NO3 − and 𝐴𝐴 n-NO3 − was generally higher than the loss of 𝐴𝐴 b-NO − retention, which caused higher fluxes of 𝐴𝐴 t-NO3 − than 𝐴𝐴 b-NO3 − (Figure 3b). Lower 𝐴𝐴 Δ 17 Ot-NO 3 − than the corresponding 𝐴𝐴 17 Ob-NO 3 − (by −4.5 ± 6.5‰ for broadleaved forests and −2.7 ± 1.5‰ for coniferous forests; Figure 4) verified the microbial nitrification within canopies as a significant 𝐴𝐴 NO3 − utor to 𝐴𝐴 t-NO3 − (Guerrieri et al, 2015(Guerrieri et al, , 2020Inoue et al, 2021;Shi et al, 2014). This finding was supported by the generally lower 𝐴𝐴 𝐴𝐴 18 Ot-NO 3 − and 𝐴𝐴 𝐴𝐴 15 Nt-NO 3 − signatures relative to the corresponding 𝐴𝐴 𝐴𝐴 18 Ob-NO 3 − and 𝐴𝐴 𝐴𝐴 15 Nb-NO 3 − values, respectively (Figure 4).…”
Section: Higher 𝑨𝑨 No𝟑𝟑 − Deposition Fluxes In Throughfall Than In Bu...mentioning
confidence: 80%
“…Ammonium ( 𝐴𝐴 NH + 4 ) in the canopy from both atmospheric deposition and mineralization of organic matter in the canopy can be a substrate of nitrification in the canopy (Guerrieri et al, 2020;Wania et al, 2002). While the genetic approaches allow measuring the abundance of nitrifying species in the phyllosphere, they cannot estimate their activity and quantify the contribution of 𝐴𝐴 n-NO3 − in canopies to 𝐴𝐴 t-NO3 − (Guerrieri et al, 2020;Inoue et al, 2021). Therefore, although canopy nitrification has been recognized as the other contributor to 𝐴𝐴 t-NO3 − , extent studies emphasized less on the exact contribution of 𝐴𝐴 n-NO3 − (Garten, 1992;Heaton et al, 1997).…”
Section: Nitrate (mentioning
confidence: 99%
See 3 more Smart Citations